A preparation method of metal anticorrosion slurry, metal anticorrosion slurry and metal anticorrosion method
By oxidative etching and hydrothermal reaction of boron nitride, boron nitride/zinc borate composite is formed and combined with organosiloxane, the problem of insufficient anti-permeability of the existing coating is solved, and the corrosion resistance of the metal anti-corrosion coating is significantly improved.
Patent Information
- Application Number
- CN202411978735.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-31
- Publication Date
- 2025-04-04
AI Technical Summary
When facing harsh environments, existing metal anti-corrosion coatings have insufficient penetration resistance and are difficult to meet the anti-corrosion needs of marine and other environments.
By oxidative etching and hydrothermal reaction of boron nitride, a boron nitride/zinc borate composite was formed and combined with organosiloxane to prepare a metal anti-corrosion slurry with improved permeability.
It improves the anti-permeability and corrosion resistance of the coating, reduces the internal interface defects of the coating, and achieves better corrosion resistance.
Smart Images

Figure BDA0005221027660000041 
Figure BDA0005221027660000051 
Figure BDA0005221027660000061
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of metal anticorrosion, and in particular to a method for preparing a metal anticorrosion slurry, the metal anticorrosion slurry and a metal anticorrosion method. Background Art
[0002] Metal materials are widely used in various industries such as rail transportation, automobiles, building materials, electrical appliances, electricity, and machinery manufacturing. Due to the corrosiveness of metals, in practical applications, metal products often need surface treatment and coating to meet the demand for metal corrosion resistance in many application fields.
[0003] Traditional metal surface anti-corrosion technologies mainly include electroplating, surface oxidation, vapor deposition, and paint coating. Electroplating has the advantages of strong coating bonding, strong corrosion resistance, and good decorative properties, but there is a problem of heavy metal ion pollution. Surface oxidation can form a corrosion-resistant passivation layer in situ on the metal surface, but its corrosion resistance and durability are insufficient. Vapor deposition can obtain high-quality anti-corrosion coatings on metal surfaces, but its production cost is high and the workpiece size is greatly limited by the equipment space.
[0004] In paint coating, organic resins are mainly used as film-forming materials to form a protective layer on the metal surface. Among them, epoxy resin is the most commonly used in metal corrosion protection. This is because epoxy resin has low water absorption and permeability, and has excellent waterproofness, chemical corrosion resistance and bonding properties. Therefore, epoxy coatings have a strong bonding ability with metals and show excellent anti-corrosion effects. However, polymer coatings represented by epoxy resins have insufficient anti-penetration ability to corrosive media due to the large molecular gap, making it difficult for a single epoxy coating to meet the corrosion protection requirements of harsh environments such as the ocean, and its corrosion resistance needs to be further improved.
[0005] From the current research, increasing the corrosion resistance of the coating is the key to improving the corrosion resistance of the coating. At present, the most effective method to improve the corrosion resistance of the coating is to fill the coating with flaky materials and extend the diffusion path of the corrosive medium in the coating, but most of the flaky materials used are single-function and only play a physical shielding role. Moreover, the flaky materials are prone to produce internal defects in the coating due to insufficient combination with the resin system, resulting in poor long-term corrosion resistance. For example, the patent application with publication number CN101362920A discloses an anti-corrosion coating material, including a main agent system and a curing agent system. In parts by weight, the components in the main agent system are: 30-50 film-forming resin, 8-15 modified toughening agent, 1-2 defoaming agent, 1-2 leveling agent, 6-10 rust stabilizer, 0.2-1 rust converter, 10-15 sub-nano flaky filler, 20-40 inorganic gelling material, and 2-4 adhesion enhancer. The patent application with publication number CN118834580A discloses an anti-corrosion coating material and its preparation method and application. The raw materials of the anti-corrosion coating material include the following components by mass: 12-20 parts of acrylic resin, 25-35 parts of epoxy resin, 8-12 parts of polyether polyol, 12-15 parts of boron carbide, 8-10 parts of modified graphene, 10-15 parts of zinc powder and 1-2.5 parts of zirconium boride. Modification of the flaky filler for anti-corrosion coating plays an important role in further improving the anti-corrosion ability of metal surface coating. Summary of the invention
[0006] In order to solve the above-mentioned technical problems existing in the prior art, the present invention provides a method for preparing a metal anti-corrosion slurry, a metal anti-corrosion slurry and a metal anti-corrosion method, which modify the flaky filler used in the anti-corrosion material to improve the anti-penetration ability and anti-corrosion performance of the coating.
[0007] The present invention provides a method for preparing a metal anticorrosion slurry, comprising the following steps:
[0008] (1) using an oxidant to oxidize and etch the filler boron nitride to obtain boron nitride nanosheets;
[0009] (2) The boron nitride nanosheets obtained in step (1) and the sodium hydroxide aqueous solution are modified under heating conditions in a water bath to obtain modified boron nitride nanosheets;
[0010] (3) adding the modified boron nitride nanosheets and zinc salt obtained in step (2) to a sodium hydroxide aqueous solution, causing zinc borate to grow in situ on the surface of the boron nitride nanosheets by hydrothermal reaction, separating and obtaining a boron nitride / zinc borate complex, and dispersing the obtained boron nitride / zinc borate complex in an alcohol aqueous solution to obtain a boron nitride / zinc borate composite dispersion;
[0011] (4) The organosiloxane undergoes a hydrolysis reaction under acidic conditions, and the formed alcoholic hydroxyl groups condense with the hydroxyl groups on the surface of the nanosheets in the boron nitride / zinc borate composite dispersion to obtain the metal anticorrosion slurry.
[0012] Principle description:
[0013] Boron nitride is thinned by oxidation etching using an oxidant to obtain boron nitride nanosheets. Hydroxyl groups are introduced on the surface of boron nitride by reacting sodium hydroxide with boron nitride under water bath heating conditions. Zinc salt is then introduced, and hydrated zinc ions react with boron atoms on the surface of boron nitride under hydrothermal conditions to form zinc borate, thereby achieving in-situ growth of nano zinc borate on the surface of boron nitride nanosheets. Boron nitride / zinc borate metal anticorrosion slurry is obtained by using organosiloxane containing epoxy groups, and alcoholic hydroxyl groups formed by hydrolysis under acidic conditions are condensed with hydroxyl groups on the surface of nanosheets.
[0014] Preferably, in step (1), the oxidant is potassium permanganate, which has strong oxidizing properties and is not easily decomposed at room temperature.
[0015] Preferably, in step (1), the average thickness of the boron nitride nanosheets is 20 to 45 nm.
[0016] Preferably, in step (2), the mass fraction of the sodium hydroxide aqueous solution used is 5% to 10%, and hydroxyl groups are introduced on the surface of the boron nitride; in step (3), the mass fraction of the sodium hydroxide aqueous solution is 1% to 3%, providing alkaline reaction conditions.
[0017] Preferably, in step (2), the mass ratio of boron nitride nanosheets to sodium hydroxide aqueous solution is 1:100-120; in step (3), the mass ratio of modified boron nitride nanosheets, zinc salt and sodium hydroxide aqueous solution is 1:0.3-1:80-120; in step (4), the mass ratio of boron nitride / zinc borate complex to organosiloxane in the boron nitride / zinc borate composite dispersion is 1:1-5.
[0018] Preferably, in step (2), the water bath heating temperature is 80-95° C., and the time is 4-8 h; in step (3), the hydrothermal reaction temperature is 140-200° C., and the time is 12-48 h.
[0019] Preferably, in step (3), the zinc salt is at least one of zinc nitrate, zinc acetate and zinc citrate; in step (4), the organosiloxane is at least one of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane (CAS: 3388-04-3), epoxycyclohexylethyl-cage polysilsesquioxane (CAS: 187333-74-0) and 3-(2,3-epoxypropyloxy)propyltrimethoxysilane (CAS: 2530-83-8).
[0020] Preferably, in step (3), the alcohol aqueous solution is an aqueous solution of at least one of ethanol, isopropanol and 2-methyl-1-propanol; the mass concentration of the alcohol aqueous solution is 85% to 95%;
[0021] The solid content of the boron nitride / zinc borate composite dispersion is 5% to 20%.
[0022] Preferably, in step (4), the pH of the boron nitride / zinc borate composite dispersion is adjusted to 5-6, and then a 10% by mass organic siloxane ethanol solution is added to react and concentrated to obtain the metal anticorrosion slurry with a solid content of 30%.
[0023] The present invention provides a metal anticorrosion slurry prepared by the preparation method.
[0024] The present invention also provides a metal anticorrosion method, wherein the metal anticorrosion slurry is uniformly mixed with epoxy resin and alcohol ether solvent to obtain a metal anticorrosion coating, and the metal anticorrosion coating is applied to a metal surface and then thermally cured to achieve metal anticorrosion. When the metal anticorrosion coating is thermally cured, the curing agent will cause the epoxy groups in the epoxy resin and the organosilicon chain segments to open, and the epoxy resin reacts with the organosilicon modified on the surface of the filler and chemically bonds, thereby achieving close bonding between the filler and the film-forming resin.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The metal anticorrosion slurry prepared by the present invention realizes the firm loading of nano zinc borate on the surface of boron nitride nanosheets, effectively integrates the physical shielding effect of boron nitride nanosheets and the anti-rust effect of zinc borate, and endows the flaky filler with multiple functions.
[0027] 2. The anticorrosive slurry prepared by the present invention has the reactivity with epoxy resin, realizes the close combination of filler and film-forming resin, reduces the internal interface defects of the coating, and improves the anti-penetration ability of the coating.
[0028] 3. The metal anti-corrosion coating prepared with the metal anti-corrosion slurry prepared by the present invention has more excellent anti-corrosion performance. DETAILED DESCRIPTION
[0029] Examples 1-8
[0030] 1. Preparation of metal anticorrosion slurry
[0031] (1) Adding boron nitride to potassium permanganate according to the formula amount, placing it in an ultrasonic oscillator with an operating frequency of 80 kHz and a power of 1500 W for treatment, filtering to obtain a precipitate; washing the precipitate with deionized water and anhydrous ethanol alternately for 3 times, and then drying it in an oven at 60° C. to obtain boron nitride nanosheets.
[0032] (2) Adding boron nitride nanosheets to a sodium hydroxide aqueous solution according to the formula amount, heating in a water bath, and filtering to obtain a precipitate; washing the precipitate alternately with deionized water and anhydrous ethanol once, and then vacuum drying at 60° C. to obtain modified boron nitride nanosheets.
[0033] (3) Adding the modified boron nitride nanosheets to a sodium hydroxide aqueous solution according to the formula amount, then adding zinc salt and magnetically stirring; then pouring the mixed solution into a hydrothermal reactor for reaction, filtering to obtain a precipitate; washing the precipitate with deionized water and anhydrous ethanol alternately for 3 times, and then dispersing it into an alcohol aqueous solution; stirring at 800 r / min for 1 hour to obtain a boron nitride / zinc borate composite dispersion with a solid content of 5% to 20%.
[0034] (4) According to the formula amount, a pH adjuster is added to the boron nitride / zinc borate composite dispersion to adjust the pH value to 5-6. When multiple pH adjusters are used at the same time, the multiple pH adjusters are mixed in equal volumes. Under the stirring condition of 500 r / min, a 10% mass fraction of an organosiloxane ethanol solution is added at a rate of 5 ml / min. After the addition is completed, stirring is continued to obtain a slurry; the slurry is filtered through a 300 mesh filter cloth, and the obtained filtrate is concentrated in a rotary evaporator to obtain a metal anticorrosion slurry with a solid content of 30%.
[0035] The specific formula quantities and process parameters of each step of preparing the metal anticorrosion slurry in Examples 1-8 are shown in Table 1.
[0036] Table 1
[0037]
[0038]
[0039]
[0040] 2. Preparation of metal anti-corrosion coatings
[0041] 40 parts by mass of epoxy resin, 60 parts by mass of metal anticorrosion slurry and 20 parts by mass of propylene glycol methyl ether were mixed and stirred for 2 hours to obtain a metal anticorrosion coating.
[0042] 3. Use of metal anti-corrosion coatings
[0043] The metal anti-corrosion coating was applied on the surface of the Q235 carbon steel metal sample by air spraying.
[0044] (1) Metal sample cleaning
[0045] The Q235 carbon steel metal sample was immersed in a 5% alkaline degreasing agent aqueous solution (BONDERITEC-AK 1022R alkaline degreasing agent produced by Henkel) to remove oil for 10 minutes, and then rinsed with deionized water; then immersed in deionized water, ultrasonically oscillated for 10 minutes, taken out and rinsed with deionized water, and dried for use.
[0046] (2) Metal sample spraying
[0047] Place the clean metal sample on the surface of the mesh spray tray and spray it by air spraying. The spraying pressure is controlled at 0.5MPa. During the spraying process, ensure that the surface coating is uniform without sagging and defects. The heat curing process after spraying is: keep warm at 80℃ for 10min; then heat up to 120℃ and keep warm for 10min; finally heat up to 150℃ and keep warm for 60min. After the coating is cured, turn the metal sample over and place it on the mesh spray tray so that the contact surface between the previous sample and the mesh spray tray is located on the outside, spray the contact surface, repeat the above spraying process and heat curing process to obtain the metal coating sample.
[0048] Comparative Example 1
[0049] Metal coating samples were prepared using the GL-925 epoxy coating produced by Jinhua Green Functional Coating Material Research Institute Co., Ltd. using the same process as that used in the metal anti-corrosion coating in Examples 1-8.
[0050] Comparative Example 2
[0051] The difference from Example 4 is that there is no step (2), and in step (3), the boron nitride nanosheets obtained in step (1) are directly dispersed in an isopropanol aqueous solution with a mass fraction of 90%; in step (4), 1 mass part of the boron nitride nanosheet dispersion is mixed with 3.6 mass parts of anhydrous ethanol, and stirred evenly at 500 r / min to obtain a slurry.
[0052] Test Example 1
[0053] According to the provisions of GB / T 10125-2021, the samples were tested for resistance to neutral salt spray. The test results of Examples 1-8 are shown in Table 1, and the test results of Comparative Examples 1-2 are shown in Table 2.
[0054] Table 2
[0055] Serial number Anti-corrosion technology Neutral salt spray resistance (h) Comparative Example 1 Traditional epoxy spraying technology 1440 Comparative Example 2 Comparative technology of the present invention 1392 Examples 1 to 8 Anticorrosion technology of the present invention 2880~3360
[0056] From the above comparison, it can be seen that compared with the existing mature epoxy spray and the comparative anti-corrosion technology of the present invention, the present invention has higher neutral salt spray resistance.
Claims
1. A method for preparing a metal anticorrosion slurry, characterized in that: The following steps are involved: (1) using an oxidant to oxidize and etch boron nitride to obtain boron nitride nanosheets; (2) The boron nitride nanosheets obtained in step (1) and the sodium hydroxide aqueous solution are modified under heating conditions in a water bath to obtain modified boron nitride nanosheets; (3) adding the modified boron nitride nanosheets and zinc salt obtained in step (2) to a sodium hydroxide aqueous solution, causing zinc borate to grow in situ on the surface of the boron nitride nanosheets by hydrothermal reaction, separating and obtaining a boron nitride / zinc borate complex, and dispersing the obtained boron nitride / zinc borate complex in an alcohol aqueous solution to obtain a boron nitride / zinc borate composite dispersion; (4) The organosiloxane undergoes a hydrolysis reaction under acidic conditions, and the formed alcoholic hydroxyl groups condense with the hydroxyl groups on the surface of the nanosheets in the boron nitride / zinc borate composite dispersion to obtain the metal anticorrosion slurry.
2. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: In step (1), the oxidant is potassium permanganate; and the average thickness of the boron nitride nanosheets is 20 to 45 nm.
3. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: In step (2), the mass fraction of the sodium hydroxide aqueous solution used is 5% to 10%; In step (3), the mass fraction of the sodium hydroxide aqueous solution is 1% to 3%.
4. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: In step (2), the mass ratio of boron nitride nanosheets to sodium hydroxide aqueous solution is 1:100-120; In step (3), the mass ratio of the modified boron nitride nanosheets, the zinc salt and the sodium hydroxide aqueous solution is 1:0.3 to 1:80 to 120; In step (4), the mass ratio of the boron nitride / zinc borate composite dispersion to the organosiloxane is 1:1-5.
5. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: The water bath heating temperature in step (2) is 80 to 95° C. and the heating time is 4 to 8 hours; In step (3), the temperature of the hydrothermal reaction is 140 to 200° C. and the time is 12 to 48 hours.
6. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: In step (3), the zinc salt is at least one of zinc nitrate, zinc acetate and zinc citrate; In step (4), the organosiloxane is at least one of 2-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, epoxycyclohexylethyl-cage polysilsesquioxane and 3-(2,3-epoxypropyloxy)propyltrimethoxysilane.
7. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: In step (3), the alcohol aqueous solution is an aqueous solution of at least one of ethanol, isopropanol and 2-methyl-1-propanol; the mass concentration of the alcohol aqueous solution is 85% to 95%; The solid content of the boron nitride / zinc borate composite dispersion is 5% to 20%.
8. The method for preparing the metal anticorrosion slurry according to claim 1, characterized in that: In step (4), the pH of the boron nitride / zinc borate composite dispersion is adjusted to 5-6, and then a 10% by mass organic siloxane ethanol solution is added to react and concentrated to obtain the metal anticorrosion slurry with a solid content of 30%.
9. The metal anticorrosion slurry prepared by the preparation method according to any one of claims 1 to 8.
10. A metal anticorrosion method, characterized in that: The metal anti-corrosion slurry described in claim 9 is evenly mixed with epoxy resin and alcohol ether solvent to obtain a metal anti-corrosion coating. After the metal anti-corrosion coating is applied to the metal surface, it is thermally cured to achieve metal anti-corrosion.
Citation Information
Patent Citations
Anticorrosion coating material
CN101362920A
Anticorrosive coating material as well as preparation method and application thereof
CN118834580A